The Evaluation Of the Syrian experience in building construction approach with the concepts of the industrialized building system and identifying aspects and factors of development - Hassan, Bassam; Beshara, Madonna (Latakia University Journal -Engineering Sciences Series, 2016)
The construction sector in Syria - especially in the field of building – is characterized by the domination of traditional methods on building systems, and thus this system is often unable to achieve the requirements and objectives of the construction. Advanced construction sector towards the basis of the construction industry requires the use of developed technology and administrative systems compatible and in harmony with the architectural and constructional and technical building so that they can get the product within modern sophisticated standards. The research aim is to evaluate the Syrian experience in building construction, and compare it with the concepts and characteristics of the industrialized building system (IBS) and determine the position of the Syrian experience regarding these concepts, as well as evaluating the factors affecting the industry. Through the evaluation , we have calculated the degree of IBS for various patterns of the executive solutions used for buildings in Syria , cast in-situ with reinforcement walls has got 13.1% , while for cast in-situ formwork system with frame structure was 34 % , and for tunnel form 64% , For the mixed system (cast in situ and precast concrete) 61%, and for the composite system (concrete and metal) 67.25%, and for prefabricated system from 82% up to 86%. Measurements obtained indicated a low level for the industrialized building system in Syria, where the majority of buildings are made using traditional methods of cast in-situ concrete. The questionnaire showed that the trend towards contemporary industrialized building system is facing significant challenges in spite of its inevitability as a strategic decision in finding solutions to the problems of housing and reconstruction. Through the search , we prioritize the use of one of the technical systems in construction in Syria using the method of the AHP. prefabricated advanced system had the first rank by 39.4% , followed in second place by mixed system (cast in situ and precast concrete) 21.8%, followed in third place by cast in-situ system with advanced technology 20.8%, as stated in the last ranking traditional tools and methods by 18.1 %.